Modern nosoareas of tick-borne encephalitis and tick-borne rickettsiosis in Siberia - V. K. Yastrebov (Бюллетень сибирской медицины, 2006)
Natural centers of tick-borne encephalitis and tick-borne rickettsiosis diseases are distinguished not only by stability and in- creasing level of epidemiological manifestation but also by ability to enlargement of areas. It is found that a contribution of some regions of Russia to the sick rate of tick-borne encephalitis and tick-borne rickettsiosis is changing in time. For tick-borne encephalitis the contribution of East Siberia increases and becomes equal to one of Ural area. For tick-borne rickettsiosis the general contribution of four regions (East Siberia, West Siberia, Ural and Far East) amount to 92% of diseases in country. The greater part of tick-borne rickettsiosis diseases (62,1%) is the contribution of East Siberia because of activi- ty of disease centers of Altai area.